ANALISIS HUKUM MENJATUHKAN PIDANA PELAKU PERCOBAAN PEMERKOSAAN : Studi Putusan Nomor 247/Pid.B/ 2021/PN.Kbu - M. Ruhly Kesuma Dinata (Universitas Muhammadiyah Kotabumi, 2020)
This study discusses the analysis of the judge's decision in imposing the criminal on the perpetrator of attempted rape (study of decision number 247/pid.b/2021/pn.kbu). The data used in this study is secondary data which includes library materials such as: documents, scientific works, books, articles, legislation, and other official documents. Other data used consist of: primary data, secondary data. The results of the research that the author has carry out the issue of the crime of attempted rape, it can be withdrawnthe following conclusions: 1. Whereas, the peak of the dispute and argument between the Plaintiff and the Defendant occurred on August 25, 2019, because the Defendant invited the Plaintiff to move and live at his parents' house but the Plaintiff was not permitted by his parents. and lives at his parents' house and the Plaintiff also stays at his parents' residence; 2. Barriers to Judges in Imposing Criminal Decisions Against Perpetrators of Attempted Rape Case Number 247/Pid.B/2021/PN.Kbu.